SOME FACTORS OF INTER WORKING ENVIRONMENTAL AND ITS RELAYTIONSHIPS WITH LEVEL OF PERFORMANCE IN AGRICULURAL COOPERATION IN SECTION OF SLAHLDEEN AGRICULTURAL DEMONSTRATION - Ali, Majid khalil (Diyala Agricultural Sciences Journal, 2013)
This study aimed to determine level of performance of workers in Agricultural cooperation in section of Slahaldeen Agricultural demonstration. and determine a relation between level of workers performance with some inter environmental work factors. also to get formation on direct and indirect effect of work environmental factors on level of performance of those agricultural workers and to know similarity between these section of Agricultural demonstration of slahadeen government Decreasing of single and bulk work pressures and human relations improvement.The study included all Agricultural workers in Agricultural extension which equaled with 14 agricultural sections. randomized sample choose by several stages with 60% from agricultural sections which sized 0f 8 sections then a sample choose by same of these workers. in these sections by 84 workers sized 50 respondent. A questionnaire used as a tool for data collecting by to parts. the first part is to get to measuring some factors of intra working environmental (single and bulk working pressure and human relationships) The second part included 32 point for measuring level of performance of the workers. which the reliability measured by split- half methods. The result showed that the level of performance of those workers was medium. appositive significant correlation present between human relationships and level of workers performance and a negative significant correlation between single pressure and level of performance while the relation was positive non significant between bulk work pressure and level of workers performance. also there were direct and in direct effect for intra work environmental factors and level of agricultural woekers performance. there were different degrees from similarity between agricultural section The study recommended with more importance for intra working environmental from the way of decreasing of single and bulk work pressures and improvement of human relationships between those workers which effected on the level of performance of workers in extension organization